E-Marketplace business model: marketing channel option for Costa Rican agro-exporters SMEs - Zerón Bascopé, Uriel (2023)
Research has shown that technological resources are essential to drive innovation and improvement processes. However, many companies resist change and do not adopt these resources as a growth strategy. Objective: Identify the incidence of use and reasons for non-use of the E-Marketplace business model as a marketing channel option in Small and Medium Enterprises (SMEs) Costa Rican agro-exporters. Methodology: Given the quantitative nature of this article, an applied descriptive-exploratory study was chosen, since relevant aspects of the incidence of use and non-use of said platforms are described. It was sought to collect data through surveys, which were answered voluntarily. Results: It was found that 91% do not put this type of online marketing into practice, the reasons; ignorance of the use of technological platforms and tools, use of traditional channels, the product does not adapt to the model, resistance to membership fees, among other aspects. This research is strategic in the face of changes that are taking place in commerce, understanding the reasons and circumstances will undoubtedly allow us to deepen our knowledge.